Monitoring and Reputation: The Choice between Bank Loans and Directly Placed Debt - Diamond, Douglas W. (Journal of Political Economy, 1991)
This paper determines when a debt contract will be monitored by lenders. This is the choice between borrowing directly (issuing a bond, without monitoring) and borrowing through a bank that monitors to alleviate moral hazard. This provides a theory of bank loan demand and of the role of monitoring in circumstances in which reputation effects are important. A key result is that borrowers with credit ratings toward the middle of the spectrum rely on bank loans, and in periods of high interest rates or low future profitability, higher-rated borrowers choose to borrow from banks.